Sistem Pakar Penentu Penyakit Gigi Dengan Metode Naive Bayes Pada RSUD Solok Selatan - Putra, Fiki Kurniawan (Universitas Multi Data Palembang, 2024)
The importance of having healthy teeth has been demonstrated by various studies, but with insufficient facilities it is difficult to the goal so that people can understand how important it is to have a healthy tooth. In collaboration with a specialist at RSUD Solok South, this research has succeeded in creating an expert system website that can help a patient to diagnose early symptoms Gingivitis, Periodontitis, Caries Superfisialis (enamel), Caries Media, as well as Deep Caries on the teeth anywhere and at any time, by implementing Naive Bayes method on the website as a calculation system and with 20 symptoms that have been concluded and obtained from the specialist that will be asked to the patient, the system will look for results based on the data of symptoms perceived against the patient.